PEMBELAJARAN BERBASIS MASALAH BERBANTUAN ISU SOSIAL LOKAL UNTUK MENINGKATKAN EMPATI SOSIAL DAN PENALARAN SOSIAL KRITIS SISWA SEKOLAH DASAR - Haniah, St; Amin, Sulvahrul; Yumriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the implementation of problem-based learning supported by local social issues to improve fourth-grade elementary students’ social empathy and socio-critical reasoning. The local issue used in this study was waste management in the school environment, including littering habits, limited waste sorting, and the impact of waste on school comfort. This research employed a quantitative pre-experimental method with a one-group pretest-posttest design. The participants consisted of 22 fourth-grade students. The intervention was conducted in eight meetings using problem orientation, group investigation, cause-and-effect analysis, solution design, presentation, and reflection. Data were collected using a social empathy scale and a scenario-based socio-critical reasoning test. The results showed that students’ mean social empathy score increased from 61.23 to 73.64, with an N-Gain of 0.32 categorized as moderate. Students’ mean socio-critical reasoning score increased from 56.59 to 68.64, with an N-Gain of 0.28 categorized as low toward moderate. These findings indicate that problem-based learning supported by local waste issues can encourage students to understand others’ perspectives, show concern for the school environment, identify social problems, analyze causes and impacts, and propose realistic solutions. Therefore, this learning model is relevant to be applied in elementary education as a contextual strategy to strengthen social-emotional competence and critical thinking.